Multi-environment field trials for wheat yield, stability and breeding progress in Germany - Tien-Cheng Wang; Till Rose; Holger Zetzsche; Agim Ballvora; Wolfgang Friedt; Henning Kage; Jens Léon; Carolin Lichthardt; Frank Ordon; Rod J Snowdon; Andreas Stahl; Hartmut Stützel; et al. (Scientific Data)
Abstract Multi-environmental trials (MET) with temporal and spatial variance are crucial for understanding genotype-environment-management (GxExM) interactions in crops. Here, we present a MET dataset for winter wheat in Germany. The dataset encompasses MET spanning six years (2015–2020), six locations and nine crop management scenarios (consisting of combinations for three treatments, unbalanced in each location and year) comparing 228 cultivars released between 1963 and 2016, amounting to a total of 526,751 data points covering 24 traits. Beside grain yield, ten agronomic traits, four baking quality traits, plant height, heading date, maturity date and six fungal disease infection indices are included. Additionally, we provide management records, including fertilizer use, plant protection measures, irrigation, and weather data. We demonstrate how this dataset can address four agronomic questions related to GxExM interactions. Further potential applications of the dataset include empirical analyses, genomic and enviromic analyses for breeding targets, or development of decision-supporting models for agricultural management and policy decisions.